Tanggung Jawab Pemerintah Daerah Terhadap Anak Terlantar - Hilda, Hilda; Pietersz, Jemmy Jefry; Sedubun, Victor Juzuf (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Legal issues in this study include, What is the form of responsibility of local governments towards abandoned children and the legal consequences that arise if local governments do not carry out responsibilities towards abandoned children.Purposes of the Research: This paper aims to describe the legal consequences if local governments do not carry out their responsibilities towards abandoned children.Methods of the Research: The type of research used is normative research, where research is carried out by collecting legal materials obtained from literature studies. The problem approach used is a statutory approach and a conceptual approach. Legal materials are analyzed qualitatively to achieve clarity on the issues to be discussed.Results of the Research: The results of this study show that Legal consequences arising if the local government does not carry out its responsibilities towards abandoned children based on Perma No. 2/2019 Article 3 that local governments can be sued on the grounds of committing illegal acts because negligence towards the responsibility of caring for abandoned children has been regulated in laws and regulations, besides that it is also contrary to the principles of good governance